A review of the genus Parorthocladius Thienemann from China (Diptera: Chironomidae: Orthocladiinae) - Liu, Yuedan; Wang, Xinhua (Zootaxa, 2005)
The males of three new species of Parorthocladius from China P. concretus sp. nov., P. cristatus sp. nov., and P. unicentrus sp. nov. are described and figured. The genus is recorded from the Oriental Region for the first time. A key to the worlds described males of Parorthocladius is presented, and the generic diagnosis is emended.